Social life of the city of karshi during the years of independence (1991–1999) - Nuritdinovich, Nurbek Mirzayev (Journal of Multidisciplinary Academic and Practice Studies, 2025)
Purpose: This study aims to analyze the social transformations that occurred in Qarshi city between 1991 and 1999, a period marked by Uzbekistan’s transition to independence. The research focuses on how political and economic reforms influenced urban social structures, education, healthcare, infrastructure, and civic life. Research Methodology: The study employs historical, comparative, and statistical analysis methods. Archival data, policy documents, and demographic statistics were examined to trace the evolution of social institutions and public services. Comparative analysis was used to identify differences between the pre- and post-independence periods, highlighting the dynamics of urban modernization. Results: The findings reveal that Qarshi experienced rapid institutional restructuring in education and healthcare, expansion of public infrastructure, and revitalization of the mahalla (neighborhood) system as a local governance unit. Cultural and civic initiatives contributed to the emergence of civil society, although disparities in access to services persisted. Conclusions: The first decade of independence represented a foundational phase of social modernization in Qarshi. While reforms fostered civic engagement and improved living conditions, the transition also revealed challenges in administrative capacity and resource distribution. Limitations: The study is limited to the 1991–1999 period and relies on available statistical data, which may not fully capture informal community dynamics. Contribution: This research provides a contextual understanding of post-independence urban transformation in regional Uzbekistan, offering insights for comparative studies on local development and nation-building.